Using Literal Translation Method in the Novel The Rise of the Underground - Yusuf, Faidah; Fajri, Mathlail (CV. Creative Tugu Pena, 2021)
Translation as applied linguistics is one of the important aspects that should be owned by every student. The aims of this article are to identify the literal translation method used in the product of translation of the novel “The Rise of the underground”. Furthermore, technique of analysis data of this research is descriptive qualitative method. The researchers found that level shift is commonly used by translator to translate the novel it can be proved with literal translation method. the researchers concluded that the Literal translation by using Newmark theory is the source language grammatical forms that are converted to their nearest target language equivalent. In addition, the tactic compromises on an appropriate meaning. So, that no assonance, or repetition jars in the translation. Translation shift helps the researchers to get easier to describe how the process of translation can be occurred in both of source and target language. The implication of this research is that students or researchers can know well about literals translation when used in novels, and can also be applied when the communication process needs to be translated. Keywords: Literal Translation. Source Language, Target Language